Oil well cement paste retarder as well as preparation and application thereof
By using polymerization technology of materials such as AMPS and azelaic acid in oil well cement slurry, an ultra-high temperature and low dilution retarder was prepared, which solved the problem of poor performance of cement slurry in high temperature and high salt environments in the prior art. The stable cementing effect in deep well ultra-deep wells was achieved.
Patent Information
- Application Number
- CN202411270955.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The cement slurry of existing oil wells is poor in high temperature and high salt environments, and it is difficult to meet the demand for deep well ultra-deep well cementing, especially under conditions of temperatures above 220℃ and high salt concentration, the thickening time is short and the strength is insufficient. There are dilution and sedimentation problems.
100-120 parts by mass of AMPS and 9-15 parts by mass of azelaic acid were polymerized under the conditions of an oxide initiator, 1-2 parts of ferrous sulfate and 4-4.3 parts of sodium sulfite were added, and dissolved in 80-90 parts of water. At 78-80 degrees Celsius, 0.1-2 parts of sodium gluconate and 0.5-3 parts of polycarboxylic acid water reducing agent were added to prepare an ultra-high temperature and low dilution oil well cement slurry retarder.
The retarder has no obvious dilution at above 220°C, has salt resistance, extends thickening time, meets the top strength requirements, and is stable under large temperature differences, avoids flocculation and settlement, and is suitable for deep well ultra-deep well cementing.
Abstract
Description
Technical Field
[0001] The invention relates to an ultra-high temperature resistant and low dilution oil well cement slurry retarder and the preparation and application thereof. Background Art
[0002] With the increasing number of ultra-deep wells in oil and gas production, the quality of the wellbore is directly related to the success or failure of the drilling project and the life of the oil and gas well. Cementing is a key technology to ensure the quality of oil and gas well projects, and cement slurry is the core technology of cementing, and it is an important means to ensure the sustainable and high-quality development of oil and gas field exploration and development. Due to the complex geological conditions, pressure system, temperature system, well depth structure and other complex problems in ultra-deep wells, it is very difficult to ensure the long-term isolation quality. In particular, the safety density window is narrow, the cementing return is difficult and the cement continuous filling is difficult, and under the conditions of high and low pressure coexistence, the cementing quality pass rate is generally low, which requires further improvement of cement slurry performance.
[0003] In recent years, polymer fluid loss additives have developed fastest among oil well cement slurry admixtures, and new reports have been continuously published in various publications and patent documents. Although many of them have been actually applied to oil field cementing and have achieved good results, such as the common LW-1, FC-03, SK-1, TD-X, TD-S, J-2B, T121, T-50A, W99 and other products, these can only be used below 160°C and can only have good effects in fresh water slurry. Summary of the invention
[0004] The present invention is made in order to further improve the adaptability of oil well cement to high temperature and high salt environment.
[0005] As one aspect of the present invention, it relates to an oil well cement slurry retarder, which is polymerized by 100-120 parts by mass of AMPS (2-acrylamide-2-methylpropanesulfonic acid) and 9-15 parts by mass of azelaic acid.
[0006] In certain specific embodiments, the oil well cement slurry retarder is polymerized under the conditions of an oxide-based initiator.
[0007] As another aspect of the present invention, it relates to a method for preparing the above-mentioned oil well cement slurry retarder, the method comprising:
[0008] (1) 100-120 parts of AMPS, 9-15 parts of azelaic acid, 1-2 parts of ferrous sulfate and 4-4.3 parts of sodium sulfite are dissolved in 80-90 parts of water; (2) 0.1-2 parts of gluconate and 0.5-3 parts of polycarboxylic acid water reducer are added.
[0009] In a specific embodiment, step (1) preferably comprises dissolving 110-120 parts of AMPS, 9-15 parts of azelaic acid, 1-2 parts of ferrous sulfate and 4-4.3 parts of sulfite in 80-90 parts of water.
[0010] In a specific embodiment, step (2) is preferably: adding 0.5-1 parts of sodium gluconate and 0.5-0.9 parts of polycarboxylate water reducer.
[0011] Step (2) is preferably carried out at 78-80 degrees Celsius.
[0012] In a specific embodiment, the gluconate is sodium gluconate.
[0013] As another aspect of the present invention, it relates to the application of the above-mentioned oil well cement slurry retarder in oil and gas development.
[0014] As another aspect of the present invention, it relates to an oil well cement, wherein the oil well cement contains the above-mentioned oil well cement slurry retarder.
[0015] As another aspect of the present invention, it relates to the application of the above-mentioned oil well cement in oil and gas development.
[0016] The ultra-high temperature resistant and low dilution oil well cement retarder provided by the present invention is used for deep wells and ultra-deep wells. When the temperature is higher than 220°C, there is no obvious dilution. When the complex salts (concentration 30%) such as potassium chloride-sodium oxalate salt are close to the saturation concentration, the retarder has certain salt resistance, effectively prolongs the thickening time, is resistant to large temperature differences, and meets the top strength requirements. Under the condition of a large temperature difference of 80°C, the top strength is not affected by the thickening time, there is no flocculation and no sedimentation, and the cementing requirements of deep wells and ultra-deep wells can be met. DETAILED DESCRIPTION
[0017] The parts referred to in this application are parts by mass unless otherwise specified.
[0018] Example 1: Take 100 parts of AMPS (2-acrylamide 2-methylpropane sulfonic acid), 10 parts of azelaic acid, 2 parts of ferrous sulfate, 4 parts of sodium sulfite, 0.5 parts of polycarboxylic acid water reducer, 0.1 parts of sodium gluconate, and 100 parts of water.
[0019] In 100 parts of water, add 100 parts of AMPS, 10 parts of azelaic acid, heat to 65 degrees Celsius, add 2 parts of ferrous sulfate, 1 part of sodium sulfite, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.5 parts of sodium gluconate and 0.1 parts of polycarboxylic acid water reducer, and the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH value is measured to be 6.9, which is neutral and meets environmental protection requirements.
[0020] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0021] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0022] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0023] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 1.
[0024] Table 1
[0025] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 ---- ---- Experimental Group 2 ---- ----
[0026] As can be seen from Table 1, the slurry could not be poured into the slurry cup of the viscometer, and the evaluation experiment could not be carried out. The retarder was incompatible with the cement.
[0027] When the salt concentration increases, the slurry cannot be poured into the viscometer slurry cup and the evaluation experiment cannot be carried out.
[0028] Example 2: Take 100 parts of AMPS (2-acrylamide 2-methylpropane sulfonic acid), 9 parts of azelaic acid, 2 parts of ferrous sulfate, 4 parts of sodium sulfite, 0.5 parts of polycarboxylic acid water reducer, 0.5 parts of sodium gluconate, and 50 parts of water.
[0029] In 50 parts of water, add 100 parts of AMPS, 10 parts of azelaic acid, heat to 65 degrees Celsius, add 2 parts of ferrous sulfate, 1 part of sodium sulfite, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.5 parts of sodium gluconate and 0.5 parts of polycarboxylic acid water reducer, and the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH value is measured to be 6.9, which is neutral and meets environmental protection requirements.
[0030] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0031] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0032] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0033] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 2.
[0034] Table 2
[0035] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 ---- ---- Experimental Group 2 ---- ----
[0036] As can be seen from Table 2, the slurry could not be poured into the slurry cup of the viscometer, and the evaluation experiment could not be carried out. The retarder was incompatible with the cement.
[0037] When the salt concentration increases, the slurry cannot be poured into the viscometer slurry cup and the evaluation experiment cannot be carried out.
[0038] Example 3: 150 parts of AMPS (2-acrylamide 2-methylpropane sulfonic acid), 9 parts of azelaic acid, 2 parts of ferrous sulfate, 4 parts of sodium sulfite, 0.5 parts of polycarboxylic acid water reducer, 0.5 parts of sodium gluconate, and 80 parts of water.
[0039] In 80 parts of water, 150 parts of AMPS and 9 parts of azelaic acid were added, the temperature was raised to 65 degrees Celsius, 2 parts of ferrous sulfate and 4 parts of sodium sulfite were added, fully dissolved, and the temperature was raised to 75 degrees Celsius. After 2 hours of heat preservation, 0.5 parts of sodium gluconate and 0.5 parts of polycarboxylic acid water reducer were added. After the addition, the temperature was raised to 80 degrees Celsius, the temperature was recorded and the temperature section was set to be kept warm for 4 hours to prepare a retarder. After the heat preservation was completed, it was cooled to room temperature, and the pH value of the polymer was measured to be 4.5, which was acidic and did not meet environmental protection requirements.
[0040] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0041] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0042] The distilled water in the above cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0043] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and included in Table 3.
[0044] Table 3
[0045] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 157 13.4 Experimental Group 2 86 5.3
[0046] As can be seen from Table 3, the thickening time of the cement slurry of Experimental Group 1 to which the retarder prepared in this embodiment was added was not significantly prolonged compared with the thickening time of the cement-based slurry of the blank control group, and the 48-hour strength was reduced; the thickening time of the cement slurry of Experimental Group 2 prepared with 18% brine and the retarder prepared in this embodiment was not significantly prolonged compared with the cement-based slurry of the blank control group, and the 48-hour strength data was reduced by 19.5 mPa.
[0047] When the salt concentration increases, the retarder prepared in this embodiment has a poor effect on extending the thickening time of cement slurry, and the 48-hour strength of the cement-based slurry decreases, and the slurry is not significantly diluted. In other words, the retarder prepared in this embodiment has no high temperature resistance and no salt resistance, and its Ph value is acidic, which does not meet environmental protection requirements.
[0048] Example 4: Take 100 parts of AMPS (2-acrylamide 2-methylpropane sulfonic acid), 20 parts of azelaic acid, 2 parts of ferrous sulfate, 4 parts of sodium sulfite, 0.5 parts of polycarboxylic acid water reducer, 0.5 parts of sodium gluconate, and 80 parts of water.
[0049] In 80 parts of water, 100 parts of AMPS and 20 parts of azelaic acid were added, the temperature was raised to 65 degrees Celsius, 2 parts of ferrous sulfate and 4 parts of sodium sulfite were added, fully dissolved, the temperature was raised to 75 degrees Celsius, and after 2 hours of heat preservation, 0.5 parts of sodium gluconate and 0.5 parts of polycarboxylic acid water reducer were added. After the addition, the temperature was raised to 80 degrees Celsius, the temperature was recorded and the temperature section was set to be kept warm for 4 hours to prepare a retarder. After the heat preservation was completed, it was cooled to room temperature, and the pH value of the polymer was measured to be 4, which was acidic and did not meet environmental protection requirements.
[0050] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0051] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0052] The distilled water in the above cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0053] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and included in Table 4.
[0054] Table 4
[0055] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 120 15.2 Experimental Group 2 57 4.7
[0056] As can be seen from Table 4, the thickening time of the cement slurry of Experimental Group 1 to which the retarder prepared in this embodiment was added was not significantly prolonged compared with the thickening time of the cement-based slurry of the blank control group, and the 48-hour strength was reduced; the thickening time of the cement slurry of Experimental Group 2 prepared with 18% brine and the retarder prepared in this embodiment was not significantly prolonged compared with the cement-based slurry of the blank control group, and the 48-hour strength data was reduced by 20.1 mPa.
[0057] When the salt concentration increases, the retarder prepared in this embodiment has a poorer effect on extending the thickening time of cement slurry, and the 48-hour strength of the cement-based slurry decreases, and the slurry has no obvious dilution. In other words, the retarder prepared in this embodiment has no high temperature resistance and no salt resistance.
[0058] Example 5: 100 parts of AMPS (2-acrylamide 2-methylpropanesulfonic acid), 6 parts of azelaic acid, 2 parts of ferrous sulfate, 4 parts of sodium sulfite, 0.5 parts of polycarboxylic acid water reducer, 0.5 parts of sodium gluconate, and 80 parts of water.
[0059] In 80 parts of water, add 100 parts of AMPS, 6 parts of azelaic acid, heat to 65 degrees Celsius, add 2 parts of ferrous sulfate, 4 parts of sodium sulfite, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.5 parts of sodium gluconate and 0.5 parts of polycarboxylic acid water reducer, and the temperature rises to 80 degrees Celsius after adding. Record the temperature and set the temperature section to keep warm for 4 hours to prepare a retarder. After the insulation is completed, cool to room temperature, and the polymer pH value is measured to be 6.9, which meets environmental protection requirements. Performance evaluation: The cement-based slurry (blank control group) is: 500g G-grade cement + 300g quartz sand + 8gGWD-1S + 336g distilled water + 1.6gGWX-1L.
[0060] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0061] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0062] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and included in Table 5.
[0063] Table 5
[0064] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 321 24.2 Experimental Group 2 242 8.5
[0065] As can be seen from Table 5, the thickening time of the cement slurry of Experimental Group 1 to which the retarder prepared in this embodiment was added was extended by 200 minutes compared with the thickening time of the cement-based slurry of the blank control group, and the 48-hour strength did not change; the thickening time of the cement slurry of Experimental Group 2 to which the retarder prepared in this embodiment was added and prepared with 18% brine was extended by 121 minutes compared with the cement-based slurry of the blank control group, and the 48-hour strength data decreased by 16.3 mPa.
[0066] When the salt concentration increases, the retarder prepared in this embodiment has a poorer effect on extending the thickening time of cement slurry, and the 48-hour strength of the cement-based slurry decreases, and the slurry has no obvious dilution. In other words, the retarder prepared in this embodiment has high temperature resistance, but no salt resistance.
[0067] Example 6: Take 100 parts of AMPS (2-acrylamide 2-methylpropane sulfonic acid), 9 parts of azelaic acid, 3 parts of ferrous sulfate, 7 parts of sodium sulfite, 0.5 parts of polycarboxylic acid water reducer, 0.5 parts of sodium gluconate, and 80 parts of water.
[0068] In 80 parts of water, 150 parts of AMPS and 9 parts of azelaic acid were added, the temperature was raised to 65 degrees Celsius, 3 parts of ferrous sulfate and 7 parts of sodium sulfite were added, fully dissolved, and the temperature was raised to 75 degrees Celsius. After 2 hours of heat preservation, 0.5 parts of sodium gluconate and 0.5 parts of polycarboxylic acid water reducer were added. After the addition, the temperature was raised to 80 degrees Celsius, the temperature was recorded and the temperature section was set to be kept warm for 4 hours to prepare a retarder. After the heat preservation was completed, it was cooled to room temperature, and the pH value of the polymer was measured to be 5, which was acidic and did not meet environmental protection requirements.
[0069] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0070] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0071] The distilled water in the above cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0072] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and included in Table 6.
[0073] Table 6
[0074] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 235 21.6 Experimental Group 2 217 17.8
[0075] As shown in Table 6, the thickening time of the cement slurry of Experimental Group 1, which added the retarder prepared in this embodiment, was 114 minutes longer than that of the cement slurry of the blank control group, and the 48-hour strength reduction was not obvious; the thickening time of the cement slurry of Experimental Group 2, which added the retarder prepared in this embodiment and prepared with 18% brine, was 96 minutes longer than that of the cement slurry of the blank control group, and the 48-hour strength data was reduced by 7 mPa. However, the cement slurries of Experimental Groups 1 and 2 both had obvious stratification, indicating that the stability of the cement slurry system was not good.
[0076] When the salt concentration increases, the retarder prepared in this embodiment has a significant effect on extending the thickening time of the cement slurry, and the strength of the cement-based slurry decreases after 48 hours, and the slurry is not significantly diluted. In other words, the retarder prepared in this embodiment has high temperature resistance and salt resistance, but the Ph value is acidic, which does not meet environmental protection requirements, and the slurry is unstable.
[0077] Example 7: Take 100 parts of AMPS (2-acrylamide 2-methylpropane sulfonic acid), 9 parts of azelaic acid, 2 parts of ferrous sulfate, 1 part of sodium sulfite, 1 part of polycarboxylic acid water reducer, 1.5 parts of sodium gluconate, and 90 parts of water.
[0078] In 90 parts of water, add 100 parts of AMPS, 9 parts of azelaic acid, heat to 65 degrees Celsius, add 2 parts of ferrous sulfate, 1 part of sodium sulfite, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 1 part of sodium gluconate and 1.5 parts of polycarboxylic acid water reducer, and the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH value is measured to be 6.7, which is neutral and meets environmental protection requirements.
[0079] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0080] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0081] The distilled water in the above cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0082] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and included in Table 7.
[0083] Table 7
[0084] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 235 21.6 Experimental Group 2 217 17.8
[0085] As shown in Table 7, the thickening time of the cement slurry in Experimental Group 1, which was added with the retarder prepared in this embodiment, was 114 minutes longer than that of the cement slurry in the blank control group, and the 48-hour strength reduction was not obvious; the thickening time of the cement slurry in Experimental Group 2, which was added with the retarder prepared in this embodiment and prepared with 18% brine, was 96 minutes longer than that of the cement slurry in the blank control group, and the 48-hour strength data was reduced by 7 mPa. However, the cement slurries in Experimental Groups 1 and 2 both had obvious stratification, indicating that the cement slurry system was not stable.
[0086] When the salt concentration increases, the retarder prepared in this embodiment has a significant effect on extending the thickening time of the cement slurry, and the strength of the cement-based slurry decreases after 48 hours, and the slurry is not significantly diluted. In other words, the retarder prepared in this embodiment has high temperature resistance and salt resistance, but the Ph value is acidic, which does not meet environmental protection requirements, and the slurry is unstable.
[0087] Example 8: Take 120 parts of AMPS (2-acrylamide 2-methylpropane sulfonic acid), 9 parts of azelaic acid, 2 parts of ferrous sulfate, 4 parts of sodium sulfite, 0.5 parts of polycarboxylic acid water reducer, 0.5 parts of sodium gluconate, and 120 parts of water.
[0088] In 120 parts of water, add 120 parts of AMPS, 9 parts of azelaic acid, heat to 65 degrees Celsius, add 2 parts of ferrous sulfate, 4 parts of sodium sulfite, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.5 parts of sodium gluconate and 0.5 parts of polycarboxylate water reducer, and the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and measure the polymer pH value to be 6.9, which is neutral and meets environmental protection requirements.
[0089] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0090] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0091] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0092] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and included in Table 8.
[0093] Table 8
[0094] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 141 21.3 Experimental Group 2 56 20.0
[0095] As can be seen from Table 8, the thickening time of the cement slurry of Experimental Group 1 to which the retarder prepared in this embodiment was added was 20 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength reduction was not obvious; the thickening time of the cement slurry of Experimental Group 2 prepared with 18% brine and the retarder prepared in this embodiment was not extended compared with the cement-based slurry of the blank control group, and the 48-hour strength data was reduced by 4.8 mPa.
[0096] When the salt concentration increases, the retarder prepared in this embodiment does not extend the thickening time of the cement slurry, and the strength of the cement-based slurry decreases after 48 hours, and the slurry is not significantly diluted. In other words, the retarder prepared in this embodiment has high temperature resistance, but no salt resistance.
[0097] Example 9: Take 100 parts of AMPS (2-acrylamide 2-methylpropane sulfonic acid), 9 parts of azelaic acid, 2 parts of ferrous sulfate, 4 parts of sodium sulfite, 0.5 parts of polycarboxylic acid water reducer, 0.5 parts of sodium gluconate, and 75 parts of water.
[0098] In 75 parts of water, 100 parts of AMPS and 9 parts of azelaic acid were added, the temperature was raised to 65 degrees Celsius, 2 parts of ferrous sulfate and 4 parts of sodium sulfite were added, fully dissolved, the temperature was raised to 75 degrees Celsius, and after 2 hours of heat preservation, 0.5 parts of sodium gluconate and 0.5 parts of polycarboxylic acid water reducer were added. After the addition, the temperature was raised to 80 degrees Celsius, the temperature was recorded and the temperature section was set to be kept warm for 4 hours to prepare a retarder. After the heat preservation was completed, it was cooled to room temperature, and the pH value of the polymer was measured to be 3, which was acidic and did not meet environmental protection requirements.
[0099] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0100] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0101] The distilled water in the above cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0102] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 9.
[0103] Table 9
[0104] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 425 6.3 Experimental Group 2 321 2.5
[0105] It can be seen from Table 9 that the thickening time of the cement slurry of Experimental Group 1 to which the retarder prepared in this embodiment is added is 304 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength is reduced by 18.5 mPa; the thickening time of the cement slurry of Experimental Group 2 prepared with 18% brine and the retarder prepared in this embodiment is 200 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength data is reduced by 22.3 mPa.
[0106] When the salt concentration increases, the retarder prepared in this embodiment has an effect of extending the thickening time of cement, but the strength of cement paste decreases significantly. This shows that the prepared retarder has the effect of extending the thickening time, but seriously affects the strength value, and the pH value is acidic and does not meet the environmental protection requirements.
[0107] Example 10: Take 100 parts of AMPS (2-acrylamide 2-methylpropane sulfonic acid), 9 parts of azelaic acid, 2 parts of ferrous sulfate, 4 parts of sodium sulfite, 0.5 parts of polycarboxylic acid water reducer, 0.5 parts of sodium gluconate, and 80 parts of water.
[0108] In 80 parts of water, add 100 parts of AMPS, 9 parts of azelaic acid, heat to 65 degrees Celsius, add 2 parts of ferrous sulfate, 4 parts of sodium sulfite, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.5 parts of sodium gluconate and 0.5 parts of polycarboxylic acid water reducer, the temperature rises to 78 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and measure the polymer pH value to be 6.9, which is neutral and meets environmental protection requirements.
[0109] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0110] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0111] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0112] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 10.
[0113] Table 10
[0114] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 350 21.3 Experimental Group 2 342 16.3
[0115] It can be seen from Table 10 that the thickening time of the cement slurry of Experimental Group 1 to which the retarder prepared in this embodiment is added is 229 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength is reduced by 3.5 mPa; the thickening time of the cement slurry of Experimental Group 2 prepared with 18% brine and the retarder prepared in this embodiment is 221 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength data is reduced by 8.5 mPa.
[0116] When the salt concentration increases, the retarder prepared in this embodiment has the effect of extending the cement thickening time.
[0117] Example 11: Take 100 parts of AMPS (2-acrylamide 2-methylpropane sulfonic acid), 9 parts of azelaic acid, 2 parts of ferrous sulfate, 4 parts of sodium sulfite, 0.5 parts of polycarboxylic acid water reducer, 2.5 parts of sodium gluconate, and 80 parts of water.
[0118] In 80 parts of water, add 100 parts of AMPS, 9 parts of azelaic acid, heat to 65 degrees Celsius, add 2 parts of ferrous sulfate, 4 parts of sodium sulfite, fully dissolve, heat to 75 degrees Celsius, keep warm for 2 hours, add 0.5 parts of sodium gluconate and 2.5 parts of polycarboxylic acid water reducer, and the temperature rises to 80 degrees Celsius after adding, record the temperature and set the temperature section to keep warm for 4 hours to prepare the retarder. After the insulation is completed, cool to room temperature, and the polymer pH value is measured to be 6.9, which is neutral and meets environmental protection requirements.
[0119] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0120] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0121] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0122] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 11.
[0123] Table 11
[0124] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 221 22.3 Experimental Group 2 151 16.8
[0125] It can be seen from Table 11 that the thickening time of the cement slurry of Experimental Group 1 to which the retarder prepared in this embodiment is added is 100 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength is reduced by 2.5 mPa; the thickening time of the cement slurry of Experimental Group 2 prepared with 18% brine and the retarder prepared in this embodiment is 30 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength data is reduced by 5.5 mPa.
[0126] When the salt concentration increases, the retarder prepared in this embodiment has the effect of extending the cement thickening time. The pH value is neutral and meets the environmental protection requirements.
[0127] Example 12: Take 100 parts of AMPS (2-acrylamide 2-methylpropane sulfonic acid), 10 parts of azelaic acid, 2 parts of ferrous sulfate, 4 parts of sodium sulfite, 0.5 parts of polycarboxylic acid water reducer, 0.1 parts of sodium gluconate, and 80 parts of water.
[0128] First, add 80 parts of water into the reaction container, raise the temperature to 75 degrees Celsius, add 100 parts of AMPS, 10 parts of azelaic acid, 2 parts of ferrous sulfate, and 4 parts of sodium sulfite. After fully dissolved, heat to 75 degrees Celsius. After keeping warm for 2 hours, add 0.1 parts of sodium gluconate and 0.5 parts of polycarboxylic acid water reducer. At this time, the temperature rises to about 80 degrees Celsius. Record the temperature and set the temperature section to keep warm for 10 hours. After the insulation is completed, cool to room temperature and measure the pH value of the polymer to be 6.9, which is neutral and meets environmental protection requirements.
[0129] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0130] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0131] The distilled water in the above cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0132] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 12.
[0133] Table 12
[0134] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 242 16.2 Experimental Group 2 181 14.3
[0135] It can be seen from Table 12 that the thickening time of the cement slurry of Experimental Group 1 to which the retarder prepared in this embodiment is added is 121 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength is reduced by 8.6 mPa; the thickening time of the cement slurry of Experimental Group 2 prepared with 18% brine and the retarder prepared in this embodiment is 60 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength data is reduced by 10.5 mPa.
[0136] When the salt concentration increases, the retarder prepared in this embodiment has the effect of extending the cement thickening time. The pH value is neutral and meets the environmental protection requirements.
[0137] Example 13: Take 100 parts of AMPS (2-acrylamide 2-methylpropane sulfonic acid), 9 parts of azelaic acid, 2 parts of ferrous sulfate, 4 parts of sodium sulfite, 3.0 parts of polycarboxylic acid water reducer, 2.0 parts of sodium gluconate, and 80 parts of water.
[0138] First, add 80 parts of water into the reaction container, add 100 parts of AMPS, 10 parts of azelaic acid, 2 parts of ferrous sulfate, and 4 parts of sodium sulfite. After fully dissolved, heat to 75 degrees Celsius. After keeping warm for 2 hours, add 2.0 parts of sodium gluconate and 3.0 parts of polycarboxylic acid water reducer. At this time, the temperature rises to about 80 degrees Celsius. Record the temperature and set the temperature section to keep warm for 10 hours. After the insulation is completed, cool to room temperature and measure the pH value of the polymer to be 6.9, which is neutral and meets environmental protection requirements.
[0139] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0140] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0141] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0142] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 13.
[0143] Table 13
[0144] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 142 15.2 Experimental Group 2 130 10.0
[0145] It can be seen from Table 13 that the thickening time of the cement slurry of Experimental Group 1 to which the retarder prepared in this embodiment is added is 21 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength is reduced by 9.6 mPa; the thickening time of the cement slurry of Experimental Group 2 prepared with 18% brine and the retarder prepared in this embodiment is 9 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength data is reduced by 14.8 mPa.
[0146] When the salt concentration increases, the retarder prepared in this embodiment has the effect of extending the cement thickening time. The pH value is neutral and meets the environmental protection requirements.
[0147] Example 14: 100 parts of AMPS (2-acrylamide 2-methylpropanesulfonic acid), 9 parts of azelaic acid, 1 part of ferrous sulfate, 4 parts of sodium sulfite, 0.5 parts of polycarboxylic acid water reducer, 0.5 parts of sodium gluconate, and 80 parts of water.
[0148] First, add 80 parts of water into the reaction container, add 100 parts of AMPS, 9 parts of azelaic acid, 1 part of ferrous sulfate, and 4 parts of sodium sulfite. After fully dissolved, heat to 75 degrees Celsius. After keeping warm for 2 hours, add 0.5 parts of sodium gluconate and 0.5 parts of polycarboxylic acid water reducer. At this time, the temperature rises to about 80 degrees Celsius. Record the temperature and set the temperature section to keep warm for 10 hours. After the insulation is completed, cool to room temperature and measure the pH value of the polymer to be 6.9, which is neutral and meets environmental protection requirements.
[0149] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0150] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0151] The distilled water in the above cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0152] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 14.
[0153] Table 14
[0154] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 380 10.0 Experimental Group 2 340 9.0
[0155] It can be seen from Table 14 that the thickening time of the cement slurry of Experimental Group 1 to which the retarder prepared in this embodiment is added is 259 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength is reduced by 14.8 mPa; the thickening time of the cement slurry of Experimental Group 2 prepared with 18% brine and added with the retarder prepared in this embodiment is 119 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength data is reduced by 15.8 mPa.
[0156] When the salt concentration increases, the retarder prepared in this embodiment has the effect of extending the cement thickening time. The pH value is neutral and meets the environmental protection requirements.
[0157] Example 15: 110 parts of AMPS (2-acrylamide 2-methylpropanesulfonic acid), 15 parts of azelaic acid, 1.5 parts of ferrous sulfate, 4.3 parts of sodium sulfite, 0.8 parts of polycarboxylic acid water reducer, 0.56 parts of sodium gluconate, and 80 parts of water.
[0158] First, add 80 parts of water into the reaction container, add 100 parts of AMPS, 15 parts of azelaic acid, 1.5 parts of ferrous sulfate, and 4.3 parts of sodium sulfite. After fully dissolved, heat to 75 degrees Celsius. After keeping warm for 2 hours, add 0.5 parts of sodium gluconate and 0.8 parts of polycarboxylic acid water reducer. At this time, the temperature rises to about 80 degrees Celsius. Record the temperature and set the temperature section to keep warm for 4 hours. After the insulation is completed, cool to room temperature and measure the pH value of the polymer to be 6.9, which is neutral and meets environmental protection requirements.
[0159] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0160] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0161] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0162] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 15.
[0163] Table 15
[0164] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 361 20.3 Experimental Group 2 351 19.0
[0165] It can be seen from Table 15 that the thickening time of the cement slurry of Experimental Group 1 to which the retarder prepared in this embodiment is added is 240 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength is reduced by 4.5 mPa; the thickening time of the cement slurry of Experimental Group 2 prepared with 18% brine and the retarder prepared in this embodiment is 230 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength data is reduced by 5.8 mPa.
[0166] When the salt concentration increases, the retarder prepared in this embodiment has the effect of extending the cement thickening time. The pH value is neutral and meets the environmental protection requirements.
[0167] Example 16: 120 parts of AMPS (2-acrylamide 2-methylpropanesulfonic acid), 10 parts of azelaic acid, 2 parts of ferrous sulfate, 4 parts of sodium sulfite, 0.9 parts of polycarboxylic acid water reducer, 1 part of sodium gluconate, and 80 parts of water.
[0168] First, add 80 parts of water into the reaction container, add 120 parts of AMPS, 10 parts of azelaic acid, 2 parts of ferrous sulfate, and 4 parts of sodium sulfite. After fully dissolved, heat to 75 degrees Celsius. After keeping warm for 2 hours, add 1 part of sodium gluconate and 0.9 parts of polycarboxylic acid water reducer. At this time, the temperature rises to about 80 degrees Celsius. Record the temperature and set the temperature section to keep warm for 4 hours. After the insulation is completed, cool to room temperature and measure the polymer pH value to be 6.9, which is neutral and meets environmental protection requirements.
[0169] Performance evaluation: The cement-based slurry (blank control group) was: 500g G-grade cement + 300g quartz sand + 8g GWD-1S + 336g distilled water + 1.6g GWX-1L.
[0170] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.
[0171] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.
[0172] The experiment was carried out at 220 degrees Celsius and 110 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time was recorded, and the 48-hour strength test values were also recorded and entered into Table 16.
[0173] Table 16
[0174] Thickening time (minutes) 48-hour strength test value (mPa) Blank control group 121 24.8 Experimental Group 1 400 21.2 Experimental Group 2 392 20.8
[0175] It can be seen from Table 16 that the thickening time of the cement slurry of Experimental Group 1 to which the retarder prepared in this embodiment is added is 279 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength is reduced by 3.6 mPa; the thickening time of the cement slurry of Experimental Group 2 prepared with 18% brine and the retarder prepared in this embodiment is 271 minutes longer than that of the cement-based slurry of the blank control group, and the 48-hour strength data is reduced by 4.0 mPa.
[0176] When the salt concentration increases, the retarder prepared in this embodiment has the effect of extending the cement thickening time. The pH value is neutral and meets the environmental protection requirements.
[0177] From the above embodiments, it can be seen that:
[0178] The viscosity of the retarder prepared in Example 1-2 is too high, and the cement slurry prepared therefrom cannot be poured into the thickening slurry cup to complete the subsequent experiments;
[0179] The retarder prepared in Example 3-4 has neither temperature resistance nor salt resistance;
[0180] The retarders prepared in Example 5 and Example 8 have temperature resistance but no salt resistance;
[0181] The retarder prepared in Example 6-7 has both temperature resistance and salt resistance, but the slurry is unstable;
[0182] The retarder prepared in Example 9 has temperature and salt resistance, and the thickening time is prolonged, but it affects the strength of cement paste, and the pH value does not meet environmental protection requirements;
[0183] The retarders prepared in Examples 10-16 have temperature and salt resistance properties;
[0184] The retarder prepared in Examples 14-16 is neutral and is an ultra-high temperature resistant and low dilution oil well cement slurry retarder. The oil well cement slurry retarder is polymerized by 100-120 parts by mass of 2-acrylamide-2-methylpropanesulfonic acid and 9-15 parts by mass of azelaic acid under oxide initiator conditions.
[0185] The retarders prepared in Examples 10-16 have temperature and salt resistance properties;
[0186] (1) 100-120 parts of AMPS, 9-15 parts of azelaic acid, 1-2 parts of ferrous sulfate and 4-4.3 parts of sodium sulfite are dissolved in 80-90 parts of water; (2) 0.1-2 parts of sodium gluconate and 0.5-3 parts of polycarboxylate water reducer are added. Step (2) is preferably reacted at 78-80 degrees Celsius.
[0187] As further preferred, in the preparation method of Examples 14-16, step (2) is:
[0188] (2) Add 0.5-1 part of sodium gluconate and 0.5-0.9 part of polycarboxylate water reducer.
[0189] The ultra-high temperature resistant low dilution oil well cement slurry retarder prepared by the present invention can be used for oil and gas production. Specifically, the ultra-high temperature resistant low dilution oil well cement slurry retarder provided by the present invention is mixed with oil well cement.
Claims
1. Oil well cement slurry retarder, characterized in that: The oil well cement slurry retarder is prepared by polymerizing 100-120 parts by mass of 2-acrylamide-2-methylpropanesulfonic acid and 9-15 parts by mass of azelaic acid.
2. The oil well cement slurry retarder according to claim 1, characterized in that: The oil well cement slurry retarder is prepared by polymerizing 100-120 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid and 9-15 parts by weight of azelaic acid under the condition of an oxide initiator.
3. A method for preparing the oil well cement slurry retarder according to any one of claims 1 or 2, characterized in that: The method comprises: (1) 100-120 parts of 2-acrylamide-2-methylpropanesulfonic acid, 9-15 parts of azelaic acid, 1-2 parts of ferrous sulfate and 4-4.3 parts of sodium sulfite are dissolved in 80-90 parts of water; (2) 0.1-2 parts of gluconate and 0.5-3 parts of polycarboxylic acid water reducer are added.
4. The method according to claim 3, characterized in that Step (1) is as follows: 110-120 parts of 2-acrylamide-2-methylpropanesulfonic acid, 9-15 parts of azelaic acid, 1-2 parts of ferrous sulfate and 4-4.3 parts of sulfite are dissolved in 80-90 parts of water.
5. The method according to claim 3, characterized in that Step (2) is: (2) Add 0.5-1 part of sodium gluconate and 0.5-0.9 part of polycarboxylate water reducer.
6. The method of claim 3, characterized in that Step (2) is reacted at 78-80 degrees Celsius.
7. The method according to any one of claims 3 or 4, characterized in that: The gluconate is sodium gluconate.
8. Use of the oil well cement slurry retarder according to any one of claims 1 or 2 in oil and gas development.
9. An oil well cement, characterized in that: The oil well cement contains the oil well cement slurry retarder according to any one of claims 1 or 2.
10. Use of the oil well cement according to claim 9 in oil and gas development.
Citation Information
Patent Citations
High-temperature-resistant copolymer oil well cement retarder and preparation method thereof
CN104403056A
Medium-high temperature delayed coagulant used for oil well cement and preparation method thereof
CN105061661A